(3GdLHQ GdeLQOs - (3LgjeI(B, (3QeVGf eMeOs; (3UbQ Ydj eMeOs ((3HjQhJs (3OGQ GdcJGH GdLOjO GdeJMOIs, 2000)
(3hgPG GdcJGH jYJHQ eONdkG LjOkG dehVhYGJ GdLHQ GdeLQO Ch ddGSJNOGe aj GdYdhe GdCNQi Ch aj JYde GdehVhY faSg(B. (3hPdc dCf GdeDda bO JYQV ajg ddehGVjY GdQFjSjI HCSdhH jZdH Ydjg GdhVhM hGdHSGWI hGdYeb aj GdHMK(B. (3ceG hCVGa GdcKjQ ef GdCeKdI eY GdMdhd dJhVjM GdCacGQ GdeOQhSI, ceG oPpqjd cd HfO HGdYOjO ef GdJeGQjf(B. (3hEVGaI Edi Pdc oPjd cd aUd HJeGQjf cKjQI heJOQLI aj GdUYhHI MJi jNJHQ GdWGdH ebOQJg Ydi age hGSJfJGL GdehVhY GdPj JfGhdg, hjJe Pdc HJMVjQ GdbGQF ddehVhYGJ GddGMbI(B. (3hGdcJGH jMJhj Ydi SJI aUhd LGAJ ehVhYGJgG ceG jdj(B: (3GdaUd GdChd hGdKGfj GMJhi Ydi GdeHGOF GdYGeI dfXQjI GdeLehYGJ(B. (3CeG aj GdaUdjf GdKGdK hGdQGHY aJqe GdJQcjR Ydi fXQjI GdReQ HGYJHGQgG eLehYI JMJ JCKjQ YedjI KfGFjI hGMOI JJUa HNhGU eYjfI(B. (3CeG GdaUd GdNGeS aJYQV ddMdbGJ HGYJHGQgG eLehYI JMJ JCKjQ YedjJjf KfGFjJjf HTQhW eYjfI(B. (3aj Mjf jJVef GdaUd GdSGOS hGdCNjQ GdeLGdGJ hMdbGJ GdMOhOjGJ(B. (3ceG jMJhj GdcJGH aj fgGjJg Ydi bGFeI HGdeUWdMGJ GdYdejI GdeSJNOeI aj GdcJGH hJYQjHgG MJi JSGYO GdbGQF Ydi Jchjf GdUhQI GdhGVMI ddehVhY HOhf dHS Ch ZehV(B.s
Keywords: (3LHQs; (3QjGVjGJs